The Influence of Psychoeduction of a Sensitive Breast Examination on Attitudes and Behaviors in Detecting Breast Cancer in Adolescent Principle of Singkawang - Yuslana Yuslana; Marsia Marsia; Dwi Sulistyawati (Jurnal Ilmiah Permas: Jurnal Ilmiah STIKES Kendal, 2020)
Breast cancer is one of the most common types of cancer in Indonesia. Early breast cancer screening can be done by breast self-examination or known as breast self-examination (BSE). Psychoeducation program is one way to increase adolescent knowledge to quickly detect signs of breast cancer so that treatment will also be done quickly. The purpose of this study is to look at the effect of psychoeducation on BSE on the Attitudes and Behaviors of young women about BSE. This research method is a quasi experimental research with control group. A sample of 60 people was divided into two groups: 30 intervention groups and 30 control groups. The results of data analysis have the effect of psychoeducation on the attitudes and behaviors of breast self-examination of female adolescents before being given treatment after being given treatment and there is the effect of psychoeducation on adolescent attitudes and behavior.